Unique Aspects of Anti-Cancer Drug Development 2017
DOI: 10.5772/intechopen.68908
|View full text |Cite
|
Sign up to set email alerts
|

Lupan-Skeleton Pentacyclic Triterpenes with Activity against Skin Cancer: Preclinical Trials Evolution

Abstract: Skin cancer is an increasingly frequent pathology, with a dangerous high percentage of malignant melanoma. The use of synthetic chemotherapy raises the problem of severe adverse effects and the development of resistance to treatment. Therefore, the use of natural therapies became the focus of numerous research groups due to their high efficacy and lower systemic adverse effects. Among natural products evaluated as therapeutical agents against skin cancer, betulinic acid was emphasized as a highly selective ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 122 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…According to various studies, BA, as well as BT molecules, fit best inside γ-cyclodextrin cavity as well as its derivative hydroxypropyl-γ-CD (HPGCD). BA water solubility increased 14 times when in complexes with HPGCD and this has also improved its antimelanoma activity as shown on the B16 cell line [4]. Soica et al [51] described BA activity in complexes with octakis-[6-deoxy-6-(2-sulfanylethanesulfone)]-γ-CD (GCDG) on metastatic and nonmetastatic B164A5 melanoma cell lines.…”
Section: In Vitro Experimentsmentioning
confidence: 98%
See 3 more Smart Citations
“…According to various studies, BA, as well as BT molecules, fit best inside γ-cyclodextrin cavity as well as its derivative hydroxypropyl-γ-CD (HPGCD). BA water solubility increased 14 times when in complexes with HPGCD and this has also improved its antimelanoma activity as shown on the B16 cell line [4]. Soica et al [51] described BA activity in complexes with octakis-[6-deoxy-6-(2-sulfanylethanesulfone)]-γ-CD (GCDG) on metastatic and nonmetastatic B164A5 melanoma cell lines.…”
Section: In Vitro Experimentsmentioning
confidence: 98%
“…It is the most dangerous type of skin cancer due to its prominent metastasis and resistance to radio-and chemotherapy [3]. Changes in lifestyle, including exposure to excessive UV radiation, have led to a significant increase in the amount of melanoma incidence and melanoma-related deaths over the years; this accounts for 75% of skin cancer deaths [4,5]. Nowadays, standard melanoma treatment is mainly based on surgical procedures (at early stages), chemotherapy, radiation, immunotherapy and targeted therapies; nevertheless, effective treatment options in melanoma are still limited [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pentacyclic triterpenes, secondary metabolites extensively found in the plant kingdom, are located in various parts of the plant, such as the bark, root and leaves. An important number of studies showed the curative potential of lupane-type pentacyclic triterpenes (Figure 3) through various biological activities such as anti-inflammatory [28,29], anticancer [30,31], antioxidant [12], antiviral [13,32], antiparasitic [33] or healing properties [17], all of them being confirmed through extensive research.…”
Section: Lupane-type Triterpenesmentioning
confidence: 99%